Enhancing Student Sustainability Awareness in Science Education: A Systematic Literature Review - M. Andriansyah; Indri Yani; Sandi Budiana; Didit Ardianto; Indarini Dwi Pursitasari (Universitas Negeri Semarang, 2025)
Sustainability awareness in secondary school students is an important element in modern education that aims to address global challenges such as climate change and environmental degradation. This study used a systematic literature review (SLR) approach to evaluate the level of sustainability awareness, the effectiveness of learning media, and the challenges of implementing sustainability-based learning. The analysis was conducted on 10 articles selected based on strict inclusion and exclusion criteria, using the PRISMA method and NVivo software. Results show that students' emotional awareness is at the highest level, followed by sustainability knowledge, while behavioral awareness is still low. Education for Sustainable Development (ESD)-based learning media proved most effective, followed by web-based applications and learning modules. Key challenges include teacher readiness, time constraints, and learning resources. The study concludes that there is a need for the integration of sustainability values in the curriculum, intensive training for teachers, and the use of innovative learning media to improve the success of sustainability education.